الفصل الخامس: مواليد القرن العشرين الميلادي (Mawalid al-qarn al-'ishrin al-Miladi) - Chik, Abdul Rahman (IIUM Press, 2011)
8 names of scholars are listed in chapter 5: Mohd Nor Ibrahim, Mohamd Nasir, Haji Abdul Malik Karim Amrullah, Ahmad Ibrahim, Yasin al-Fadani, Aminuddin Baki, S.Osman Kelantan, and Mahmud Saedon Awang Osman.